Heteroglossic Masculinity in Haruki Murakami’s ‘A Wild Sheep Chase’ - Laura Emily Clark (New Voices in Japanese Studies, 2017)
Studies on Japanese masculinity have been consistently and strongly engaged with R. W. Connell’s (1995) theory of the gender order and hegemonic masculinity, with the Japanese salaryman being identified as a masculine ideal by a number of scholars. Within this context there has been an emphasis on the plurality of masculinities present within society, and the instability of masculine ideals in gendered performances across different contexts. I argue, however, that there is still space to engage more deeply with Bakhtin’s concept of heteroglossia in order to reveal a multitude of different masculine voices present within a single gendered performance. Studies on the literature of Haruki Murakami have had only limited engagement with issues of masculinity, therefore this paper also demonstrates the potential for analysing the voices of male characters in fiction through masculinity theory. Here, I undertake a discourse analysis of three male characters in Haruki Murakami’s A Wild Sheep Chase [1982], proposing that although these characters are strongly engaged and invested in the monoglossic salaryman masculinity, there is always a heteroglossia of masculine performances present. This suggests that plurality is not actually an exception, or evidence of a failure to comply, but rather an ordinary aspect of gendered performance.